Analisis Faktor Faktor Yang Mempengaruhi Kepuasan Kerja Perawat (Studi Empiris di RSP TNI AU Dr. S. Hardjolukito Yogyakarta) - Wolo, Petrus Dala; , Dra. Rina Trisnawati, Ak, M.Si. PhD; , Drs. Wiyadi, MM. PhD (2015)
Job satisfaction is a perception of a person or employee on the job if the job can be satisfy or unsatisfy. The role of nurses in a hospital is very important as the executor of medical treatment so it is important for a hospital to give attention to the level of job satisfaction as a result of the work he was doing. This study aims to determine the effect of salary, promotion, supervision, co-workers, work itself, and the work environment on job satisfaction of nurses in RSP TNI AU Dr. S. Hardjolukito Yogyakarta. The population in this study was nurses in RSP TNI AU Dr. S. Hardjolukito Yogyakarta as many as 96 people. While the sample is taken from a nurse who served in inpatient unit including Camar room, Merak room, Kasuari room and Parkit room as many as 71 people. The analysis method used in this research is multiple linear regression with the sampling technique using proposive sampling. The results showed that there is a significant relationship between the work itself and the work environment on job satisfaction. While salary, promotion, supervision, and co-workers have not effect on job satisfaction. Of the work itself and the work environment to job in RSP TNI AU Dr. S. Hardjolukito Yogyakarta has to give more attention to working conditions that make nurses feel attracted and respect for his job as well as the condition of the working room comfortable, quiet and give attention to equipment that allows nurses to carry out the task.